PENYIMPANAN BAHAN PERISHABLE DI COLD KITCHEN SECTION NOVOTEL PEKANBARU - Arief Pratama Yudha; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Storage system is a way to preserve things in order to make it easier to undertake the job. A hotel has to keep tabs on the perishable material storage system that it manages. This study aims to determine how important the concerns of the perishable material storage system, the perishable material storage SOP, perishable material storage facility, and stock card stock/logbook of entry and exit of perishable materials are, which in this case the theory in reference to Utari's (2009) at the Cold Kitchen section of Novotel Pekanbaru. The details were collected using interview, observation and documentation techniques. Based on the research, it was found that the perishable material storage system in the Cold Kitchen section of Novotel Pekanbaru is considered balanced, meaning that there has been an increment according to the standards that have been set as well as some deficiency based on the standard itself. Keywords: Storage System, Perishable Materials, Cold Kitchen Section, Novotel Pekanbaru.